Is Bargaining a Form of Deliberating? - Ani, E.I. (Philosophical Papers, 2020)
Prevailing literature argues that arguing is the only appropriate mode of deliberation. The literature acknowledges bargaining, storytelling, and other forms of communication, but is unwilling to describe these as deliberation, properly speaking. The claim is that describing them as such would amount to concept stretching. My first thesis is that arguing exhausts neither the legitimate modes of deliberation nor the modes for effective deliberation. To do this I further develop a two-type categorization of issues I have employed elsewhere to show that argument alone is sufficient for bringing closure to issues in the first category, but bargaining is needed to reach agreements on issues in the second category. I observe that the more agreeable variant of the second category of issues constitutes a great deal of issues deliberated outside the purely theoretical classroom. Progressing from these observations, my second thesis is that bargaining is in fact the preeminent way of reaching agreements in political deliberation. To illustrate this, I demonstrate that normative differences and distributive consequences are inherent features of political issues.
Research Article
Keywords: communication; bargaining; deliberation; exchange of arguments